Comparing available rainfall gridded datasets for West Africa and the impact on rainfall-runoff modelling results, the case of Burkina-Faso. - (:unkn) unknown (My University, 2008)
Monthly rainfall data in Burkina-Faso, West Africa, over a period of 77 years are extracted from three different gridded data sets, available either on the web: CRU (Climatic Research Unit, Norwich, UK), SIEREM (HydroSciences Montpellier, France), or from the National Meteorological Center of Burkina-Faso. With a view to model the runoff-rainfall relationship at the monthly time step, these data are used at the 0.5↓0.5↓ scale. The three grids have very similar means, standard deviation and interannual variability for the period 1922 to 1998, but some differences are observed which lead to significantly different runoff-rainfall simulations. These differences are linked to the absolute values: the more important the rainfalls are, the less the differences are; and to the density of the rainfall station network which also has a strong influence on the areal rainfall estimation, that can be worked out between 2 to 12%, according to the data sets used. The conclusion is that it is recommended to use as many stations as possible to better assess areal rainfall. These biases have a strong influence on the results of the runoff-rainfall modelling (using the GR2M conceptual model): the Nash criteria show differences of about 20% and calculated flow of 30% to 40%. This study illustrates the levels of uncertainty when using available rainfall gridded data sets, for rainfall-runoff studies in West African developing countries, which is important in the context of predicting water resources for the future from the GCM outputs for the XXIst century.
Keywords: African Research